Biogeochemistry of manganese in ferruginous Lake Matano, Indonesia - C. Jones; S. A. Crowe; A. Sturm; K. L. Leslie; L. C. W. MacLean; S. Katsev; C. Henny; D. A. Fowle; D. E. Canfield (Biogeosciences, 2011)
This study explores Mn biogeochemistry in a stratified, ferruginous lake, a modern analogue to ferruginous oceans. Intense Mn cycling occurs in the chemocline where Mn is recycled at least 15 times before sedimentation. The product of biologically catalyzed Mn oxidation in Lake Matano is birnessite. Although there is evidence for abiotic Mn reduction with Fe(II), Mn reduction likely occurs through a variety of pathways. The flux of Fe(II) is insufficient to balance the reduction of Mn at 125 m depth in the water column, and Mn reduction could be a significant contributor to CH4 oxidation. By combining results from synchrotron-based X-ray fluorescence and X-ray spectroscopy, extractions of sinking particles, and reaction transport modeling, we find the kinetics of Mn reduction in the lake's reducing waters are sufficiently rapid to preclude the deposition of Mn oxides from the water column to the sediments underlying ferruginous water. This has strong implications for the interpretation of the sedimentary Mn record.